2019
DOI: 10.1111/pai.13055
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to antiepileptic drugs in children

Abstract: Background Antiepileptic drugs (AEDs) can cause hypersensitivity reactions in children. These reactions are mainly cutaneous, self‐limiting, and benign, but life‐threatening severe cutaneous adverse reactions can occur. Infections can lead to skin eruptions and mimic drug hypersensitivity reactions, if a drug is taken at the same time. The aims of our study were to confirm or rule out the diagnosis of hypersensitivity reactions to AEDs in children and to detect an infection which mimics these reactions. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…23 In addition to the chemical structure of the drug (aromatic rings), risk factors which are important for the development of HRs to AEDs include age and gender, history of previous AED reactions, viral infections, concomitant medications, and genetic factors. 1,2,24 Age-related differences in drug metabolism (the reduction in glucuronide conjugation in infants, faster rate of CYP-mediated reactions in infants and children) may result in an increase in hypersensitivity to AEDs in young children. 5,[25][26][27][28] Children younger than 5 years of age have up to 5 times higher risks for development of SCARs and rashes induced by AEDs.…”
Section: Immune Pathomechanis Ms Ris K Fac Tor S and G Ene Ti C Smentioning
confidence: 99%
See 3 more Smart Citations
“…23 In addition to the chemical structure of the drug (aromatic rings), risk factors which are important for the development of HRs to AEDs include age and gender, history of previous AED reactions, viral infections, concomitant medications, and genetic factors. 1,2,24 Age-related differences in drug metabolism (the reduction in glucuronide conjugation in infants, faster rate of CYP-mediated reactions in infants and children) may result in an increase in hypersensitivity to AEDs in young children. 5,[25][26][27][28] Children younger than 5 years of age have up to 5 times higher risks for development of SCARs and rashes induced by AEDs.…”
Section: Immune Pathomechanis Ms Ris K Fac Tor S and G Ene Ti C Smentioning
confidence: 99%
“…It remains controversial as to whether the herpes viral infection or reactivation of the latent viral genome is a triggering cofactor, or a result of HR to the drug itself. 1,2 A few pediatric studies showed the significant associations between certain HLA alleles and AED-induced HRs such as in Thai children 37 HLA-A*01:01 and HLA-B*13:01 and PHB hypersensitivity, in 37,40 Specifically, several genomewide association study investigations from Han Chinese (Taiwan), 41 European, 40,41 Canadian (mixed ethnicity), 39 Spanish Romani, 42 and Korean 43 confirmed a strong HLA-A* 31:01 association with CBZ-induced DRESS and/or MPE, but not for SJS/TEN.…”
Section: Key Messagementioning
confidence: 99%
See 2 more Smart Citations
“…Considering that there are no specific tests to distinguish between a viral infection and DHRs in the acute phase, a diagnostic work‐up should be performed to remove a false label of hypersensitivity 4 . DHRs diagnosis is complex, time consuming, needs to be done by trained staff, and it is not standardized for many drugs.…”
Section: Introductionmentioning
confidence: 99%